Development planning, financing and outcomes of metropolitan arrangements the case of Metro Naga Development Council - Lopez, Divina Luz J.; Magnaye, Dina C. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
The study characterized and evaluated metropolitan arrangements for development planning and financing (the processes) and its influence on the existing local planning process and on-socioeconomic development (the outcomes). Using the case of Metro Naga Development Council, it elaborated on the institutional arrangements for planning (and financing) under a metropolitan set up and described metro-level complementation with local level planning. The study is able to document how the various components of metropolitan planning and financing reinforce and complement to generate the desired institutional and economic development changes. This research is also able to enhance the Good Metro Governance and Sustainable Urban Development (GMGSUD) Framework developed by Manasan and Mercado (1998) by adding a set of indicators in assessing the metropolitan structure in relation to metro planning and management. The experience of MNDC as documented by the study, lend some bases to the claim by the same author that linkages among government organizations are crucial in extending services and facilities and in serving as channels for obtaining political support essential to pursue local and area-wide development (Rondinelli). How the MNDC is able to demonstrate the metropolitan task of establishing systematic coordination mechanisms for planning and for mobilizing funds for metro-based priorities under a disjointed political jurisdiction set-up is also captured in the documentation. The research is able to affirm the importance of full local ownership by the LGUs and other key stakeholders in their decision to form the MNDC (MA). It has documented hot the metropolitan arrangements in the Council contributed to achieving institutional gains - capacity developed, convergence and partnerships forged to sustain its existence in the last twenty-five (25) years since it was formed. Lastly, the study presented a set of recommendations to enhance the link between metropolitan planning and financing on one hand, and the local planning system on the other hand, building on existing policies promoting complementation and harmonization in planning and investments programming.
Thesis (Ph.D. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Metropolitan government -- Philippines -- Naga (Bicol).; Urban planning -- Philippines -- Naga (Bicol).; City planning -- Philippines -- Naga (Bicol).